Nurses’ perceptions of their professional rights - Kangasniemi, Mari; Stievano, Alessandro; Pietilä, Anna-Maija (2013)
The purpose of this study, which is part of a wider study of professional ethics, was to describe nurses’ perceptions of their rights in Italy. The data were collected by open-ended focus group interviews and analyzed with inductive content analysis. Based on the analysis, three main themes were identified. The first theme “Unfamiliarity with rights” described nurses’ perception that their rights mirrored historical roots, educational content, and nurses’ and patients’ position in the society. The second theme, “Rights reflected in legislation” highlighted that working and professional Italian legislation played a strong role. The third theme, “Managerial barriers for nurses’ rights” underlined the nurses’ perceptions that nursing management had the responsibility to create the conditions where nurses’ rights could flourish. This study intends to contribute to the debate on this underexplored topic.
Keywords: Rights; professional rights; Professional Ethics; Nurses; Legislation; Human Rights